The Effectiveness of The Video Critic Method in Multiple Intelligences-Based Learning for VIII Class Students at Madrasah Tsanawiyah - Sutipyo Ru'iya; Yusron Masduki; Amrih Latifah (Universitas Kanjuruhan Malang, 2022)
Strategy is important in the learning process to encourage student success. The teacher's expertise in compiling and using appropriate-strategies with learning materials will increase the effectiveness of learning. This study is a pre-experimental design study, intending to know the effectiveness of the video critic method in multiple intelligences-based-learning in class VIII students at Madrasah Tsanawiyah. The sample used was 30 students that choosen by random sampling. The data collection instrument was a cognitive test. The data analysis technique used a different test